2014
DOI: 10.3758/s13421-014-0425-y
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval speeds context fluctuation: Why semantic generation enhances later learning but hinders prior learning

Abstract: In recent work, retrieval has been shown to enhance memory for events following that retrieval. In this set of experiments, we examined the effects of interleaved semantic retrieval on both previous and future learning within a multilist learning paradigm. Interleaved retrieval led to enhanced memory for lists learned following retrieval. In contrast, memory was impaired for lists learned prior to retrieval (Experiment 1). These results are consistent with recent work in multilist learning, directed forgetting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
51
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 42 publications
6
51
2
Order By: Relevance
“…There is no specification of the nature of these cues or what causes them to fluctuate (cf. Divis & Benjamin, 2014). Yet, it is interesting to consider what sorts of operational variables might reflect this overlap.…”
Section: Discussionmentioning
confidence: 99%
“…There is no specification of the nature of these cues or what causes them to fluctuate (cf. Divis & Benjamin, 2014). Yet, it is interesting to consider what sorts of operational variables might reflect this overlap.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, according to the contextchange account of LMDF, which assumes that the forget cue enhances the difference between the two list contexts, and the view that mental context fluctuates over time (e.g., Estes, 1955;McGeoch, 1932), a music-or pictures-induced context change may shift the context sufficiently far away from the list contexts, so that the difference between the two list contexts may become relatively small and List-1 recall may no longer depend much on the originally induced mental context change, that is, the forgetting of List-1 items disappears (Divis & Benjamin, 2014;Mensink & Raaijmakers, 1988). Such proposal, however, does not only predict that List-1 forgetting should disappear when music or pictures are provided during the retention interval, but does also predict that List-1 recall in the remember condition should be impaired in the music and pictures conditions, relative to the counting and calculation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…One of the more curious findings in the field is that TPNL may indeed ensue not only after retrieving the previously studied material (episodic retrieval), but also after the retrieval of information unrelated to the studied material from semantic (Divis & Benjamin, 2014;Pastötter et al, 2011), or even short-term memory (Pastötter et al, 2011), although there have been unsuccessful attempts at replication (e.g. Weinstein, McDermott, Szpunar, Bäuml, & Pastötter, 2015).…”
Section: Nonepisodic Recallmentioning
confidence: 99%
“…They found that only the three forms of retrieval induced TPNL. In their first experiment, Divis and Benjamin (2014) adapted the procedure from Pastötter et al (2011).…”
Section: Nonepisodic Recallmentioning
confidence: 99%
See 1 more Smart Citation